Teachers’ Perceptions of the Teaching of Speech Acts and Pragmatics in the EFL Classroom at the Algerian Higher Education Institutions - Bounab, Farida (Journal of Human Sciences, 2022)
The present research aims to investigate the Algerian higher education teachers’ attitudes towards the teaching of pragmatics, in general, and speech acts, in particular, in the English as a foreign language classroom. Specifically, it examines the teachers’ views with regard to the teaching of speech acts and their related pragmatic knowledge in their classrooms. To help achieve the research goal, a sample population of 39 teachers participated in this study and answered a 25-item questionnaire. Findings revealed that the majority of teachers found that the teaching of speech acts and their associated pragmatic elements is important as part of teaching English; however, when it comes to the inclusion of these elements in their classrooms, they do not incorporate them frequently and on a regular basis. Thus, more efforts should be made to ensure the teaching of these pragmatic issues and the development of the learners’ pragmatic competence.